2015
DOI: 10.1007/s40692-015-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in students’ learning achievements and awareness through residence energy saving game-based inquiry playing

Abstract: Energy consumption and conservation is one of the important topics in Energy Education, whereby students are required to understand the factors of energy consumption leading to promote students' awareness on saving energy in residence. Moreover, inquiry-based learning strategy can be used to encourage students' learning in the topic. Although, several researchers studied on how to use digital games to improve understand the topic. However, a few studies have been conducted to investigate what the gender differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
4
24
0
1
Order By: Relevance
“…The findings among others were that the two experimental groups, those that use computers and the group that use tablets significantly outperformed the control group over posttest scores; the experimental group that utilised tablets significantly performed better than the group that used computers on the posttest and gender of the children had no significant influence on their posttest. Some other studies also found no significant difference in student learning outcomes based on gender [14,25,26,27,28,29,31].…”
Section: Constructivism and Sex-associated Sgla Of Senior Secondary Smentioning
confidence: 89%
See 1 more Smart Citation
“…The findings among others were that the two experimental groups, those that use computers and the group that use tablets significantly outperformed the control group over posttest scores; the experimental group that utilised tablets significantly performed better than the group that used computers on the posttest and gender of the children had no significant influence on their posttest. Some other studies also found no significant difference in student learning outcomes based on gender [14,25,26,27,28,29,31].…”
Section: Constructivism and Sex-associated Sgla Of Senior Secondary Smentioning
confidence: 89%
“…There was no significant interaction of treatment and sex over student learning achievement in biology. Dorji, Panjaburee and Srisawasdi [29] focused on the exploration of the main effect of Residential Energy Saving battle (RES-battle) on student learning achievement and awareness of energy-saving in physics. The findings established that the RES-battle was efficacious in practically minimizing the awareness and learning achievement gap in energy-saving across student gender.…”
Section: Constructivist-based Instructional Models and Gender-associamentioning
confidence: 99%
“…c) Achievement reward: Users are rewarded with a cue for unlocking the achievement. Usually, these achievements are visible to players (AlSkaif et al, 2018;Barbosa et al, 2017;Bartle, 1996;Casals et al, 2017;Chou, 2015;Dorji et al, 2015;ecoGator, 2016;Fijnheer and Van Oostendorp, 2016;Game | 2020Energy, 2018Geelen et al, 2012;Hamari and Eranti, n.d.;Matallaoui et al, 2015;Ouariachi et al, 2019;Stieglitz et al, 2016). Game-related: Players earn points toward the maximum achievement points possible as a manner to dispose and accumulate high-value rewards (Bartle, 1996).…”
Section: Knowledge Base Phasementioning
confidence: 99%
“…As stated by [27], the use of game as a means of delivering educational content to the student's consciousness is more effective. A number of studies have proven the effectiveness of gaming and gamification implementation of learning materials across various instructional medium [28][29] [30][31]. The studies on the effects of gaming application in the T&L process are summarised in Table 2 as follows:…”
Section: Learning Materials For Vocabulary Learningmentioning
confidence: 99%
“…Researchers Increasing knowledge [31], [32], [33], [34], [35], [36] Improving visual and motion skills [37], [38] Awareness about health care [39], [40] Improving technological literacy skill [41], [42] Enhancing management and administrative skills [43] Social skills [28], [44] A research by [45] highlighted that infusing a creative process in the T&L of vocabulary would make students more autonomous in expanding their knowledge because the practical experience required of creative process which could enhance students' understanding and knowledge retention. The creative process could also divert students' attention to explore something new based on problem solving.…”
Section: Effect Of Gaming and Gamification Implementationmentioning
confidence: 99%